2015
DOI: 10.1126/science.aac9593
|View full text |Cite
|
Sign up to set email alerts
|

Tissue residency of innate lymphoid cells in lymphoid and nonlymphoid organs

Abstract: Innate lymphoid cells (ILC) contribute to barrier immunity, tissue homeostasis, and immune regulation at various anatomical sites throughout the body. How ILCs maintain their presence in lymphoid and peripheral tissues is currently unknown. We found that in the lymphoid and non-lymphoid organs of adult mice, ILC are tissue-resident cells that were maintained and expanded locally under physiologic conditions, upon systemic perturbation of immune homeostasis, and during acute helminth infection. However, at late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
699
5
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(760 citation statements)
references
References 34 publications
46
699
5
10
Order By: Relevance
“…In response to systemic viral infection, memory NK cells distributed through the whole body might efficiently mediate viral control. Using parabiosis experiments, it was recently reported that not only ILCs but also subsets of NK cells carrying markers of conventional NK cells are tissue resident in different organs including the small intestine, lung and salivary gland 70 . It will be important to further dissect and characterize NK cell subsets in different organs, to understand their relationship to conventional NK cells and ILCs and to unravel their unique functionality and memory potential during disease.…”
Section: Tissue Localization Patterns Of Memory Nk Cellsmentioning
confidence: 99%
“…In response to systemic viral infection, memory NK cells distributed through the whole body might efficiently mediate viral control. Using parabiosis experiments, it was recently reported that not only ILCs but also subsets of NK cells carrying markers of conventional NK cells are tissue resident in different organs including the small intestine, lung and salivary gland 70 . It will be important to further dissect and characterize NK cell subsets in different organs, to understand their relationship to conventional NK cells and ILCs and to unravel their unique functionality and memory potential during disease.…”
Section: Tissue Localization Patterns Of Memory Nk Cellsmentioning
confidence: 99%
“…ILC3 have a long half‐life in tissues and lymph nodes and are largely replenished locally within the tissue 30, 52. Surprisingly, ILC3 can maintain their phenotype and function even in the absence of ROR γ t expression and persist for a significant length of time 53.…”
Section: Tissue‐resident Ilc3: From Cradle To Gravementioning
confidence: 99%
“…The highly active renewal capability of skin epidermis and intestinal epithelium affords rapid repopulation and recovery of barrier tissue continuity, and a repertoire of adaptive and innate immunity plays an essential role in the maintenance of barrier function and homeostatic relationship with microbes (3,4). Barrier tissues maintain resident memory T cells (5,6), innate lymphoid cells (7), and macrophages (8), which are highly specialized and capable of proliferating locally without contributions from distantly localized precursor cell populations. Infections and injuries to barrier tissues immediately activate the tissue-resident cells initiating the immune cascade.…”
mentioning
confidence: 99%